SISTEM INFORMASI ADMINISTRASI PEMBAYARAN SEKOLAH TERINTEGRASI BARCODE READER DENGAN METODE BERORIENTASI OBJEK BERBASIS CLIENT SERVER - Priyadi Priyadi; Budi Santoso (Elkom : Jurnal Elektronika dan Komputer, 2022)
Recording financial transactions is an important activity that must be carried out by a business. In accounting, recording financial transactions is a fundamental thing that must be done. With these records, all business financial transactions can be accounted for and brought to the financial statements. Computerized technology using barcodes in payment transactions has the aim of increasing speed, accuracy, and service quality. In carrying out payment administration activities still using the manual system will have an impact on the Administrative officer having difficulty finding data on students who want to pay and the network (LAN) has not been implemented on the computer is also a problem at the research site, because to share data with the treasurer and principal becomes constrained, data can be damaged, lost or misused because its security is not guaranteed. In solving these problems, the researchers collected data and facts that existed at the research site, then designed a payment administration information that was in accordance with the needs of the school. In making Administrative Information System Integrated With Barcode Reader, researchers used Microsoft Visual Basic 6.0 programming language, MySQL Server database as data storage media and Subtime Text as tools to create source code. In the preparation of this application using object-oriented methods.